Application of Graphene-Based Materials for Ammonium Removal from Aqueous Solution - Mirahsani, Arghavan (Université d'Ottawa / University of Ottawa, 2019)
High levels of ammonium in water sources pose many environmental problems. Among current technologies used for ammonium removal, adsorption/ion-exchange is potentially a viable method. There is very limited information in the literature on application of graphene based materials as an adsorbent for ammonia. The main aim of this research was to investigate the application of graphene based material as an efficient adsorbent for ammonium removal from liquid phase, to optimize the ammonium uptake, and assess the feasibility of immobilizing the graphene on a solid surface. In the first phase of this study, graphene oxide (GO) was synthesized according to an improved Hummer’s method. The as-prepared material was treated by sodium hydroxide in order to create some sodium containing functional groups on the surface of adsorbent, which show high tendency to be exchanged with ammonium cations. The adsorbent was characterized by different characterization techniques such as Raman, FT-IR, XPS, and TEM in order to identify the properties of the material before and after adsorption process. These showed the typical peaks and morphology of graphene oxide material and adsorption of ammonium identified by reduction of sodium peaks and increase in nitrogen signal. Also, isotherms, kinetics, and thermodynamics studies were performed to investigate the adsorption behavior of sodium functionalized graphene oxide (GO-Na). The isotherm was best described by a Langmuir model with maximum capacity of 32 mg/g, which is higher than capacity for many common used adsorbents such as zeolites and resins reported in literature. Furthermore, the kinetic studies revealed that the process was very fast (reaching equilibrium within 5 minutes) and a pseudo-second order model was the best fit for this adsorption process. Thermodynamic data showed that the process was an exothermic and spontaneous reaction in the nature. The second phase of this research was the investigation of the impacts of two critical factors (pH and temperature) on the adsorption of ammonium by GO-Na. Respond surface methodology was utilized to assess the effect and optimize these two parameters on the solid phase concentration and the removal percentage of the adsorbent. The optimum pH and temperature to reach the maximum values for R% (58.23%) and qe (27.45 mg/g) were predicted by the model at 8 and 45 ◦C, respectively. The results showed that temperature does not have a significant impact on the adsorption process, however, pH and the interaction of pH and temperature play a significant role in the adsorption process. In the third phase of this study, the isothermic behavior of competitive ions including calcium, potassium, and sodium on GO-Na in a single-component and multi-component system was investigated. The Langmuir isotherm model was used to fit all the experimental results. The results showed that the maximum Langmuir adsorption capacities follow the order K+ ≥ NH4+ > Ca2+ in single-component systems. In the multi-component system most of active sites were occupied by calcium cations, which limit the adsorption capacity of ammonium and potassium. A slight improvement in the contribution of ammonium removal from the multi-component system was detected by increasing the pH from 7 to 8.5, which can be explain by generation of additional favorable active sites for ammonium adsorption and formation of amide group on the surface of adsorbent in presence of OH- ions. The regeneration studies of the used material obtained from multi-component system showed a constant adsorption capacity for both ammonium and potassium and a sudden reduction in calcium uptake from 1.5 to 0.7 meq/g in the first cycle, while it remained constant in the next cycles. Finally, different kinds of sodium alginate-graphene oxide hydrogel beads were made in order to immobilize the GO powder. Results were not satisfactory for two main reasons. First, the immobilization caused a reduction in the number of sites of GO available for adsorption. Second, calcium ions (necessary for bead formation) block ammonium adsorption.
Keywords: Graphene Oxide; Adsorption; TAN Removal; Isotherms; Kinetics; Thermodynamics; Optimization; pH; Temperature; Competitive Adsorption; Ammonium; Sodium; Potassium; Calcium; Regeneration; Wastewater Treatment